Tracking Microbial Diversity and Hygienic-Sanitary Status during Processing of Farmed Rainbow Trout (Oncorhynchus mykiss) - Salud María Serrano Heredia; Javier Sánchez-Martín; Verónica Romero Gil; Francisco Noé Arroyo-López; Antonio Benítez-Cabello; Elena Carrasco Jiménez; Antonio Valero Díaz (Foods, 2023)
Aquaculture is becoming a strategic sector for many national economies to supply the increasing demand for fish from consumers. Fish culture conditions and processing operations can lead to an increase in microbial contamination of farmed fish that may shorten the shelf-life of fish products and byproducts, and ready-to-eat fishery products. The objective of this study was to evaluate the hygienic-sanitary status of water, environment, and processing of fresh-farmed rainbow trout (Oncorhynchus mykiss) fillets produced in a local fish farm in Andalusia, Spain. To achieve this, a longitudinal study was carried out by collecting environmental (air and food-contact surfaces), water from fish ponds, and rainbow trout samples. Thereby, seven sampling visits were performed between February 2021 and July 2022, where foodborne pathogens and spoilage microorganisms, together with physicochemical parameters, were analysed in the collected samples. Further, microbial identification of microbiota was achieved through a culture-dependent technique using blast analysis of 16S RNA gene sequencing. The results showed that Listeria monocytogenes and Salmonella were not detected in the analysed samples. Regarding the hygienic-sanitary status of the fish farm, the slaughtering bath, the eviscerating machine and the outlet water from fish ponds presented the highest counts of coliforms, Enterobacteriaceae, and Aerobic Mesophilic Bacteria. Staphylococcus aureus and sulphite-reducing Clostridium were identified in the conveyor belts, fish flesh, and viscera. The 16S RNA identification confirmed the presence of viable spoilage bacteria such as Citrobacter gillenii, Macrococcus caseolyticus, Hafnia paralvei, Lactococcus lactis, Lactococcus cremoris, Klebsiella, Escherichia coli, Morganella morganii, and Shewanella. Three of these genera (Citrobacter, Hafnia, and Pseudomonas) were present in all types of samples analysed. The results evidenced potential transmission of microbial contamination from contaminated packaging belts and boxes, evisceration and filleting machines to flesh and viscera samples, thus the establishment of control measures should be implemented in fish farm facilities to extend the shelf-life of farmed fishery products.